Public Spaces and Identity Construction: The Experience of Montes de Oca - Rodríguez-Gutiérrez, Johnny (2020)
Development and urban planning, in a world increasingly globalized and characterized by digital communication and the predominance of social networks, has a direct impact on the nature of public spaces -especially when one thinks in terms of the Greek agora- and in the construction of identity in the communities; which affects citizen participation. In that sense, the public space in the condominiums, and in general in the neighborhoods, becomes a place where interaction between people does not necessarily take place for public debate about community problems. But, above all, the public space is replaced by the non-public space that is in the shopping centers and other non-public spheres. Faced with this, local governments do not adopt public policies that encourage citizen interaction. The Montes Oca canton is a good example of the way in which public spaces are used today.